Exercise ECG testing in patients without known ischemic heart disease: predictors of ischemia of downstream vasodilator stress cardiac magnetic resonance. (14th October 2021) - Merenciano Gonzalez, H; Marcos-Garces, V; Gabaldon-Perez, A; Lorenzo-Hernandez, M; Nunez-Marin, G; Gavara, J; Perez, N; Rios-Navarro, C; De Dios, E; Bonanad, C; Racugno, P; Lopez-Lereu, M P; et al.
Abstract: Background: In routine clinical practice, patients with chest pain and suspected stable ischemic heart disease (SIHD) usually undergo an exercise ECG stress test (ExECG) for ischemia detection. However, since the sensitivity of this technique is relatively low, concerns exist that many patients could remain underdiagnosed. We intend to assess the clinical and ExECG predictors of ischemia on subsequent vasodilator stress cardiac magnetic resonance (vs-CMR) to help select which patients should undergo downstream testing after an initial ExECG. Material and methods: We retrospectively included 197 patients without previous history of ischemic heart disease who underwent an ExECG and a subsequent vs-CMR in the year after this test and who didn't undergo a revascularization procedure in this time frame. Clinical, ExECG and vs-CMR variables were included in the registry. vs-CMR was considered positive if ischemia was evident in at least one myocardial segment on stress first-pass perfusion without concomitant necrosis on late gadolinium enhancement imaging. We performed univariate and multivariate analysis to check for the association of variables with the risk of ischemia on vs-CMR. Results: Mean time from ExECG to vs-CMR was 88.69±84.32 days and 37 vs-CMR were positive for ischemia. Male sex, less exercise time, less % of maximum predicted exercise capacity, less maximum double product (heart rate x systolic blood pressure) and less double product reserve (DPR = maximum double product - basal double product) were associated with ischemia on vs-CMR on univariate analyses. However, the only independent predictors of ischemia on vs-CMR on multivariate binary logistic regression were male sex (HR 2.62 [CI 95%: 1.13–5.76], p=0.016) and less DPR (HR 0.90 [CI 95%: 0.84–0.97] per 1000 increase, p=0.006). The risk score derived from these two variables had a moderate predictive power (ROC curves, AUC 0.657, p=0.003). The best cut-off point for the DPR was 12400, as derived from the Youden index. It allowed stratification of the risk of ischemia on vs-CMR, which ranged from 9% in women with >12400 DPR, 18.8% in men with >12400 DPR, 24.1% in women with ≤12400 DPR to 42.9% in men with ≤12400 DPR (p=0.005, Figure 1). Conclusions: Male sex and less double product reserve on ExECG can moderately predict the risk of ischemia on subsequent vs-CMR in patients presenting with chest pain and without previous SIHD. This can help select patients who benefit most from vs-CMR for diagnostic purposes. FUNDunding Acknowledgement: Type of funding sources: None.